1982
DOI: 10.1530/jrf.0.0660699
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone feedback on FSH secretion in male sheep

Abstract: Summary. Testosterone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This aggregation effect will be less pronounced in the perfused tissue used in the present study as space left after shrinkage of the seminiferous epithelium is partly accounted for by the dilated lymphatics. Kerr, Rich & de Kretser (1979) have confirmed the impressions of earlier workers (Hanes, 1911;Lynch & Scott, 1951) (Chemes, Ri varóla & Bergada, 1976;Christensen & Peacock, 1980 (Schanbacher, 1979a;1980 (Schanbacher, 1979b;D'Occhio, Schanbacher & Kinder, 1982 (Catt et al, 1980) and an LHRH-like factor produced by the seminiferous tubule (Sharpe, Fraser, Cooper & Rommerts, 1981) have been shown to exert an intratesticular control of Leydig cell steroidogenesis, the relationship between these substances and Leydig cell structure and function has not yet been investigated. The role of the seminiferous epithelium in exerting some control of Leydig cell activity has been emphasized by Ucci (1982), who showed that there was an inverse relationship between Leydig cell size and activity, and germ cell maturation in the normal urodele testis.…”
Section: Morphometrysupporting
confidence: 72%
“…This aggregation effect will be less pronounced in the perfused tissue used in the present study as space left after shrinkage of the seminiferous epithelium is partly accounted for by the dilated lymphatics. Kerr, Rich & de Kretser (1979) have confirmed the impressions of earlier workers (Hanes, 1911;Lynch & Scott, 1951) (Chemes, Ri varóla & Bergada, 1976;Christensen & Peacock, 1980 (Schanbacher, 1979a;1980 (Schanbacher, 1979b;D'Occhio, Schanbacher & Kinder, 1982 (Catt et al, 1980) and an LHRH-like factor produced by the seminiferous tubule (Sharpe, Fraser, Cooper & Rommerts, 1981) have been shown to exert an intratesticular control of Leydig cell steroidogenesis, the relationship between these substances and Leydig cell structure and function has not yet been investigated. The role of the seminiferous epithelium in exerting some control of Leydig cell activity has been emphasized by Ucci (1982), who showed that there was an inverse relationship between Leydig cell size and activity, and germ cell maturation in the normal urodele testis.…”
Section: Morphometrysupporting
confidence: 72%
“…The alternative possibility that infused 5a-dihydrotestosterone altered LH release indirectly by displacing endogenous testosterone from its plasma binding sites is unlikely under these equilibrium conditions, since injected 5a-dihydrotestosterone actually decreases plasma free testosterone concentrations in men within 24-48 h (54). As important, the selectivity of this infusion schedule in suppressing LH pulse frequency without reducing LH pulse amplitude closely mimics the effects of low-dosage (but not pharmacological dosage) androgen replacement in other species, such as the rodent, sheep, and Rhesus monkey (55)(56)(57).…”
Section: Discussionmentioning
confidence: 89%
“…Oestradiol is also a potent inhibitor of FSH as shown by the immunization of rams (Sanford, 1987) and by replacement studies in rams (Sanford & Robaire, 1990), bulls ) and stallions (Thompson et al 1979). The relative importance of testosterone and oestradiol is unclear, as replacement of physiological levels of testosterone to recently castrated rams resulted in FSH concentrations that were within the physiological range (D'Occhio et al 1982), whereas oestradiol is more effective than testosterone alone in long-term castrated animals (D'Occhio, Galil, Brooks & Setchell, 1985), giving rise to the theory that the pituitary gland becomes insensitive to testosterone feedback with time after castration. In the stallion, however, oestradiol was more potent than testoster¬ one in short-term castrated animals, possibly reflecting the high secretion rate of testicular oestrogens in this species (Thompson et al 1979).…”
Section: Malesmentioning
confidence: 99%